Pemilihan Prioritas Penanganan Banjir Di Kecamatan Bogor Tengah Kota Bogor Provinsi Jawa Barat - Fahmi Nur Rahman; Eka Wardhani (Jurnal Serambi Engineering, 2020)
As time goes, the pace of growth and social functioning of the physical and socio-economic areas of Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi) experienced rapid development, so the policy of national spatial and policy The provincial spatial of West Java emphasized the need for adequate infrastructure development to make the city of Bogor ideal as a buffer area (hinterland) of DKI Jakarta. Referring to the condition of development dynamics of Bogor City, two important things to consider are changes in land use and spatial planning, because city drainage problems arise due to these changes. then to anticipate these problems, it is necessary to immediately review the Bogor City drainage masterplan, and it is necessary to study the material and formulate alternative solutions in the area that will be prioritized for handling. This study aimed to discuss about the arrangement of areas that will be prioritized for handling, based on Peraturan Menteri Pekerja Umum No. 12 Tahun 2014 about concerning Procedures for Planning a City Drainage System. This study can be used as a recommendation to determine priority areas for Central Bogor District.